Cost-Effectiveness Evaluation of Add-on Empagliflozin in Patients With Heart Failure and a Reduced Ejection Fraction From the Healthcare System's Perspective in the Asia-Pacific Region - Liao, Chia-Te; Yang, Chun-Ting; Kuo, Fang-Hsiu; Lee, Mei-Chuan; Chang, Wei-Ting; Tang, Hsin-Ju; Hua, Yi-Ming; Chang, Hung-Yu; Chen, Zhih-Cherng; Strong, Carol; Ou, Huang-Tz; Toh, Han Siong (Frontiers in Cardiovascular Medicine, 2021)
Background EMPEROR-Reduced trial provides promising evidence on the efficacy of empagliflozin adding to the standard treatment in patients with heart failure and reduced ejection fraction (HFrEF). This study aimed to investigate the cost-effectiveness of add-on empagliflozin versus standard therapy alone in HFrEF from the perspective of the Asia-Pacific healthcare systems. Methods A Markov model was constructed to simulate HFrEF patients and to project the lifetime direct medical costs and quality-adjusted life years (QALY) of both therapies. Transitional probabilities were derived from the EMPEROR-Reduced trial. Country-specific costs and utilities were extracted from published resources. Incremental cost-effectiveness ratio (ICER) against willingness to pay (WTP) threshold was used to examine the cost-effectiveness. A series of sensitivity analyses was performed to ensure the robustness of the results. Results The ICERs of add-on empagliflozin versus standard therapy alone in HFrEF were US20,508, US24,046, US8,846, US53,791, US21,543, and US20,982 per QALY gained in Taiwan, Japan, South Korea, Singapore, Thailand, and Australia respectively. Across these countries, the probabilities of being cost-effective for using add-on empagliflozin under the WTP threshold of 3-times country-specific gross domestic product per capita were 93.7% in Taiwan, 95.6% in Japan, 96.3% in South Korea, 94.2% Singapore, 51.9% in Thailand, and 95.9% in Australia. The probabilities were reduced when shortening the time horizon, assuming the same cardiovascular mortality for both treatments, and setting lower WTP thresholds. Conclusion Adding empagliflozin to HFrEF treatment is expected to be a cost-effective option among the Asia-Pacific countries. The cost-effectiveness is influenced by the WTP thresholds of different countries.